Upaya Meningkatkan Teknik Dasar Dribbling Bola Futsal Dengan Metode Latihan Driil Variasi Passing Pada Peserta Didik Di Sdn 32 Kabupaten Rejang Lebong - Ferdiansyah, Agil; Ajayati, Titi; Syaputra, Roni (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to improve basic futsal dribbling techniques using a dribbling drill variation training method for students at SDN 32 Rejang Lebong District. The study involved 20 subjects. The method used in this study was classroom action research. The research procedure consisted of four stages: planning, implementation, observation, and reflection. From the first cycle, after calculations were made, the results showed an improvement in the “very good” category with 5 participants (25%), the “good” category with 7 participants (35%), the ‘average’ category with 6 participants (30%), and 2 participants in the “poor” category. The number of participants who achieved mastery in the first cycle was 12 participants, representing 60%. After implementing the intervention through drill-based learning using a ball and zig-zag movements without a ball, the second cycle yielded results showing an improvement, with 12 participants in the “very good” category, 5 participants in the ‘good’ category, and 3 participants in the “average” category. The number of participants who achieved proficiency in the second cycle was 17 participants in the very good category, representing 85% of the students at SDN 32 Rejang Lebong District. It can be concluded that there is an improvement in dribbling skills through the use of learning interventions among students at SDN 32 Rejang Lebong District.